The rediscovery of an archaeological mummy site that inspired Gauchin and Munch - Ziemendorff, Stefan (2019)
It has been previously shown that a Peruvian Chachapoyan mummy has exerted an enormous influence upon the world of modern art, specifically the works of Paul Gauguin and Edvard Munch. Not only is Munch’s famous «The Scream» inspired by this ancient artifact; the mummy has has been directly and indirectly inspiring artists around the world for more than a century. Because of its role in modern art history, it is vitally important to understand and collect all the facts related to the origin and history of the mummy, especially how it was found and how it came to Paris in the late nineteenth century. Additionally the mummy is now known as the remains of a Chachapoyan warrior.